A new species of Velarifictorus (Pseudocoiblemmus) from Thailand (Gryllidae; Gryllinae; Modicogryllini) with key to species - Tan, Ming Kai; Dawwrueng, Pattarawich; Artchawakom, Taksin (Zootaxa, 2015)
One new species of Velarifictorus (Pseudocoiblemmus) is described from Thailand: Velarifictorus (Pseudocoiblemmus) bilobus sp. n. A key to all known species of Velarifictorus (Pseudocoiblemmus) is provided.